Synergistic Interactions Between Phenolic Compounds Identified in Grape Pomace Extract with Antibiotics of Different Classes Against Staphylococcus Aureus and Escherichia Coli - Wilkens-Anwandter, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Maisey-Munoz, K; Montero, R (Public Library of Science, 2017)
Synergy could be an effective strategy to potentiate and recover antibiotics nowadays useless in clinical treatments against multi-resistant bacteria. In this study, synergic interactions between antibiotics and grape pomace extract that contains high concentration of phenolic compounds were evaluated by the checkerboard method in clinical isolates of Staphylococcus aureus and Escherichia coli. To define which component of the extract is responsible for the synergic effect, phenolic compounds were identified by RP-HPLC and their relative abundance was determined. Combinations of extract with pure compounds identified there in were also evaluated. Results showed that the grape pomace extract combined with representatives of different classes of antibiotics as β-lactam, quinolone, fluoroquinolone, tetracycline and amphenicol act in synergy in all S. aureus and E. coli strains tested with FICI values varying from 0.031 to 0.155. The minimal inhibitory concentration (MIC) was reduced 4 to 75 times. The most abundant phenolic compounds identified in the extract were quercetin, gallic acid, protocatechuic acid and luteolin with relative abundance of 26.3, 24.4, 16.7 and 11.4%, respectively. All combinations of the extract with the components also showed synergy with FICI values varying from 0.031 to 0.5 and MIC reductions of 4 to 125 times with both bacteria strains. The relative abundance of phenolic compounds has no correlation with the obtained synergic effect, suggesting that the mechanism by which the synergic effect occurs is by a multi-objective action. It was also shown that combinations of grape pomace extract with antibiotics are not toxic for the HeLa cell line at concentrations in which the synergistic effect was observed (47 μg/mL of extract and 0.6-375 μg/mL antibiotics). Therefore, these combinations are good candidates for testing in animal models in order to enhance the effect of antibiotics of different classes and thus restore the currently unused clinical antibiotics due to the phenomenon of resistance. Moreover, the use of grape pomace is a good and low-cost alternative for this purpose being a waste residue of the wine industry. Copyright: © 2017 Sanhueza et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.